Bright Blue Photoluminescence Emitted from the Novel Hyperbranched Polysiloxane‐Containing Unconventional Chromogens. Issue 10 (15th February 2016) - Niu, Song; Yan, Hongxia; Li, Song; Xu, Peilun; Zhi, Xiaoli; Li, Tingting
Abstract : A blue fluorescence‐emitting hyperbranched polysiloxane simultaneously containing hydroxyl and epoxy groups (HPHEp) has been developed through one‐step A2 + B3 melt polycondensation between methoxyl groups of (3‐glycidyloxypropyl)trimethoxysilane (A‐187) and hydroxyl groups of neopentyl glycol under catalyst‐free conditions. The emission intensity of the HPHEp in ethanol solution continuously arises in pace with raising its concentration, and the brightest luminescence is observed even in the 100% solid state. Studies show that the aggregation of oxygen‐rich heteroatoms from the hydroxyl and epoxy groups is assigned to the luminous source. Intriguingly, the HPHEp displays reinforced photoluminescence after polyetherification by 20 wt% polyether amine M2070; nevertheless, the modified polymer represents diminished emission intensity along with increasing the polyether content. Thus, this investigation offers a new methodology of designing photoluminescent materials. Abstract : A novel hyperbranched polysiloxane simultaneously containing hydroxyl and epoxy groups (HPHEp) is fabricated by one‐step A2 + B3 polycondensation between methoxyl groups of (3‐glycidyloxypropyl)trimethoxysilane and hydroxyl groups of neopentyl glycol. Intriguingly, the prepared polymer incorporating unconventional chromophores can emit bright blue fluorescence in the 100% solid state. Impressively, the HPHEp exhibits enhanced photoluminescence after polyetherification by polyether amine M2070.